Effect of Oil Type Used in Neapolitan Pizza TSG Topping on Its Physical, Chemical, and Sensory Properties - Amalia Piscopo; Angela Zappia; Antonio Mincione; Roccangelo Silletti; Carmine Summo; Antonella Pasqualone (Foods, 2022)
Background: According to the regulations of the Neapolitan Pizza TSG, extra virgin olive oil must be exclusively used as topping ingredient, together with tomato for pizza marinara-type production. As, often deliberately, other oils are replaced by pizza makers for economical and organoleptic purposes, the present study was conducted to analyze the quality of pizza depending on the oil typology used. Methods: Chemical and sensory analyses were performed on olive oils and on pizza topping mix samples after cooking to detect changes due to the applied cooking processing. Results: The results revealed the best quality of a monovarietal olive oil (Ottobratica cv.) for their peculiar phenolic content related to the best oxidation stability after pizza’s cooking, expressed as bioactive amounts and lower presence of undesired volatile compounds. Conclusions: The use of an extra virgin monovarietal olive oil, such as Ottobratica cv., in the topping of pizza is preferable to other oils, also EVOO, because of its higher quality, which is reflected in greater health and pleasant characteristics from a sensorial point of view.